2012
DOI: 10.1371/journal.pone.0035613
|View full text |Cite
|
Sign up to set email alerts
|

ABC Transporters B1, C1 and G2 Differentially Regulate Neuroregeneration in Mice

Abstract: BackgroundATP-binding cassette (ABC) transporters are essential regulators of organismic homeostasis, and are particularly important in protecting the body from potentially harmful exogenous substances. Recently, an increasing number of in vitro observations have indicated a functional role of ABC transporters in the differentiation and maintenance of stem cells. Therefore, we sought to determine brain-related phenotypic changes in animals lacking the expression of distinct ABC transporters (ABCB1, ABCG2 or AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 69 publications
1
43
0
Order By: Relevance
“…Thus, the thyroid hormone receptor Tshr and PomC, a polypeptide hormone precursor that controls feeding and body weight (59), are down-regulated in Hmgn3 tm1/tm1 brain tissue, and Trib3, a putative protein kinase, implicated in hyperglycemia and glucose intolerance (60, 61) is down-regulated in the Hmgn3 tm1/tm1 liver. Muscle tissues were not analyzed in Hmgn3 tm1/tm1 mice in this study, and only weak expression was previously reported in skeletal muscle (50). The reduced grip strength detected only in Hmgn3tm1/tm1 mouse mutants could therefore be a secondary effect to differences in energy metabolism found in these mutants and not in Hmgn1 tm1/tm1 or Hmgn5 tm1/tm1 mice.…”
Section: Hmgn Variants Fine Tune the Fidelity Of The Cellular Transcrmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, the thyroid hormone receptor Tshr and PomC, a polypeptide hormone precursor that controls feeding and body weight (59), are down-regulated in Hmgn3 tm1/tm1 brain tissue, and Trib3, a putative protein kinase, implicated in hyperglycemia and glucose intolerance (60, 61) is down-regulated in the Hmgn3 tm1/tm1 liver. Muscle tissues were not analyzed in Hmgn3 tm1/tm1 mice in this study, and only weak expression was previously reported in skeletal muscle (50). The reduced grip strength detected only in Hmgn3tm1/tm1 mouse mutants could therefore be a secondary effect to differences in energy metabolism found in these mutants and not in Hmgn1 tm1/tm1 or Hmgn5 tm1/tm1 mice.…”
Section: Hmgn Variants Fine Tune the Fidelity Of The Cellular Transcrmentioning
confidence: 62%
“…The potentially altered neuronal differentiation could be directly connected to the behavioral phenotype of the Hmgn1 tm1/tm1 mice shown in Table 1. It has recently been demonstrated that modified levels of neuronal progenitor differentiation can be associated with modified levels of exploratory activity akin to the rearing/exploration phenotype observed here (50 mice. In addition, Hmgn1 tm1/tm1 mice are deficient in the repair of damaged DNA leading to hypersensitivity to both UV and ionizing radiation and to an increased incidence of certain tumors (20,21).…”
Section: Hmgn Variants Fine Tune the Fidelity Of The Cellular Transcrmentioning
confidence: 77%
“…ABC transporters mediate the export of numerous substances (peptides, drugs or drug conjugates, and hydrophobic molecules) through the blood-brain barrier, and they are expressed in each cell type in the brain (Pahnke et al, 2014;Schumacher et al, 2012). The relationship between ABC transporters and neurodegenerative diseases was commonly based on the function of ABC transporters or impairment of their function in the blood-brain barrier.…”
Section: Figmentioning
confidence: 99%
“…Paraffi n-embedded, 4-μm-thick sections were deparaffi nized and conventionally stained with hematoxylin-eosin (H&E) stain. Immunohistochemical analysis was performed according to our previous publications [52][53][54][55][56][57][58] using a BOND-MAX (Leica Microsystems GmbH/Menarini, Germany) with antibodies against ionized calcium-binding adapter molecule 1 (IBA1, 1:2,000, Wako 019-19741, Germany) to label microglia, glialfi brillary acid protein (GFAP, 1:1,000, DAKO Z033401, Germany) to label astrocytes, myelinbasic protein (MBP, 1:1,600, DAKO A062301, Germany) to label myelin sheets, neurofi lament (NF200; 1:160, Sigma-Aldrich N4142-.5ML, Germany) to label axons, NeuN (1:1,000, Millipore MAB377, Germany) to label neurons, and anti-Toxo (1:200, Dianova DLN-16734, Germany) to label T. gondii. Slides were developed using the Bond™ Polymer Refi ne Detection kit (Menarini/Leica, Germany).…”
Section: Histopathologymentioning
confidence: 99%